Effect of single and dual heat–moisture treatments on the gelatinization properties and crystalline structure of normal corn starch. (29th March 2016) - Shang, MengShan; Chen, HaiHua; Wang, YuSheng; Li, QianQian
Abstract : The gelatinization properties and crystalline structure of normal cornstarch (NCS) to which a single heat–moisture treatment (SHMT) and a dual heat–moisture treatment (DHMT) had been applied were investigated. NCS was modified by SHMT (adjusted to 25% moisture and heated at 120°C for 6 h) and DHMT (after SHMT, samples were stored at 25, 4, or −20°C for 12 h, then heated at 120°C for 1 h). The pasting properties, gel hardness, gelatinization properties, and crystalline structure of NCS were then analyzed. The results showed that the pasting viscosities of NCS subjected to SHMT and DHMT were lower than those in the original sample. SHMT and DHMT increased the onset, peak, conclusion temperature, gelatinization temperature range, and gel hardness of NCS, but reduced gelatinization enthalpy. Neither SHMT nor DHMT changed the crystalline type of NCS. DHMT with interval stored at 25 (DHMT25) and 4°C (DHMT4) were found to significantly influence the properties of NCS, compared to SHMT. On the other hand, DHMT with interval stored at −20°C (DHMT–20) was found to impose similar trends on the properties of NCS, compared to those imposed by SHMT.